Performances afro-brasileiras na cidade de Goiás (GO): diálogos patrimoniais - Macedo, Eliene Nunes (2021)
The present thesis seeks to explain black performances in some Afro-Brazilian groups from Cidade de Goiás (GO) and how they relate to the world heritage title given to the city by UNESCO and IPHAN. In such sense, the research followed the Congo, Afoxé, Avó Delê and Bloco Pilão de Prata groups to understand, in a dialogical perspective, the identity relations and their mirrors, as well as the embodiment and experiences of ethnic racial relations in heritage performance practices taking into consideration the way cultural policies are developed both worldwide and nationally with local specifications. Goiás was considered a UNESCO World Heritage in 2001 thanks to the preservation of its historical, architectonic and urbanistic values, which witnessed the occupations and colonization that happened in the 18th Century. Paradoxically, at the beginning of the 20th Century, other cultural practices start to emerge and build connections with the descolonialism context besides instigating discussions about ethnic racial relations. Such scientific investigation is justified by the need of understanding the ethnic racial identity relations that exist in post-modernity and thereby it attempts to reflect upon the multiple processes of identification and manifestations of expression that run through the aforementioned subjects. In addition to these discussions illuminating reflections on ethnic-racial relations, it underlines the emerging need for Brazilian society to critically reflect and act in the fight against racism. The analysis presented has a field research done between 2016 and 2020 as a reference in which ethnographic methods were used and whose goal is to interpret Afro-Brazilian performances in the town of Goiás and their heritage dialogues. It is possible to observe that the historical center heritage speech, which had a unique identity, starts to get fissured and displaced. As far as it is concerned, the groups Congo, Bloco do Pilão de Prata and Afoxé Avó Delê attribute new outlines to the local cultural practices and highlight the agency of symbolic content in Afro-Brazilian manifestations, which therefore result in a complex process of descolonialism as an outcome of their performances and educational actions.